2010
DOI: 10.1002/jctb.2340
|View full text |Cite
|
Sign up to set email alerts
|

Development of an original approach to evaluate effects of surfactants, biomass and pollutants on the scaling‐up of a two‐phase partitioning bioreactor

Abstract: BACKGROUND: Two-phase partitioning bioreactors (TPPBs) are considered as a new technology for xenobiotic degradation in gaseous effluents. However, there is still a need for more knowledge on how to design and scale up TPPBs. The partitioning of the two phases remains a misunderstood method of research. In particular, the impact of pollutant (isopropylbenzene), biomass and surfactant extract needs to be better evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Even though the Rhodococcus strain shows strong adherence to oil because of its hydrophobicity, migration of some of the cells into the oil phase makes this emulsion less stable and reduces the volume of the emulsion ( Déziel et al, 1999). Previously, other authors had evaluated the absorption of biomass into the oil phase obtaining a value of about 30% absorption, using a medium composed of 10% v/v silicone oil ( Aldric et al, 2010). The amount biomass that can be absorbed into the organic phase will presumably depend on the characteristics of the biomass and the physical properties of the oil, among others.…”
Section: Influence Of Silicone Oil Concentration On the Uptake Of Biomass From The Aqueous Phasementioning
confidence: 99%
“…Even though the Rhodococcus strain shows strong adherence to oil because of its hydrophobicity, migration of some of the cells into the oil phase makes this emulsion less stable and reduces the volume of the emulsion ( Déziel et al, 1999). Previously, other authors had evaluated the absorption of biomass into the oil phase obtaining a value of about 30% absorption, using a medium composed of 10% v/v silicone oil ( Aldric et al, 2010). The amount biomass that can be absorbed into the organic phase will presumably depend on the characteristics of the biomass and the physical properties of the oil, among others.…”
Section: Influence Of Silicone Oil Concentration On the Uptake Of Biomass From The Aqueous Phasementioning
confidence: 99%
“…Some recent studies have shown that the addition of an organic liquid phase, such as silicone oil, for the removal of poorly water soluble pollutants may significantly increase reactor performance (Aldric et al, 2010, Djeribi et al, 2005, Fazaelipoor and Shojaosadati, 2002, Kennes et al, 2009aand Rocha-Rios et al, 2010. In such systems, the hydrophobic organic phase acts as a reservoir, used to absorb poorly water-soluble organic pollutants from gaseous streams (Darracq et al, 2010, Daugulis, 2001and Kennes et al, 2009b.…”
Section: Introductionmentioning
confidence: 99%
“…Solid polymer beads have been shown to significantly improve the operability of TPPBs compared with immiscible liquids because they are universally biocompatible and do not suffer from emulsion formation in the presence of biomass 15. Association of the cell membrane with a dispersed immiscible liquid phase results in an emulsion which traps a significant portion of the biomass away from the aqueous phase, negatively impacting productivity as well as analytical procedures 15–17. The presence of silicone oil complicates the quantification of products distributed between the two phases, which has been identified as a major hurdle in this bioproduction system 5…”
Section: Introductionmentioning
confidence: 99%